2020
DOI: 10.1111/rec.13055
|View full text |Cite
|
Sign up to set email alerts
|

A tale of two green walls: a functional trait approach to assess vegetation establishment on restored steep slopes

Abstract: Green walls (GWs) have been increasingly recognized as an important restoration technique for steep slopes resulting from quarrying activities or major infrastructure construction projects. In practice, GW irrigation is considered essential, although studies evaluating vegetation establishment under different irrigation regimes are lacking. Besides taxonomic metrics, functional diversity measures were used to compare the diversity and composition of plant communities of two hydroseeded GWs, with different irri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 70 publications
(89 reference statements)
0
3
0
1
Order By: Relevance
“…The bryophyte searches did not yield useful information, although several of the returned papers used Ellenberg indicator values (e.g., Rajandu et al, 2021;Rola et al, 2021); however, these are considered to be ecological preferences rather than plant traits and we did not consider these further (Violle et al, 2007). Instead, we selected traits based on similar studies investigating succession found using alternate search terms in Google Scholar (Fernández-Martínez et al, 2019;Laine et al, 2018;Monteiro et al, 2020). The selected traits, length, perennation, life form, sporophyte frequency and maximum spore diameter, were extracted from BRYOATT (Hill et al, 2007).…”
Section: Species Traitsmentioning
confidence: 99%
“…The bryophyte searches did not yield useful information, although several of the returned papers used Ellenberg indicator values (e.g., Rajandu et al, 2021;Rola et al, 2021); however, these are considered to be ecological preferences rather than plant traits and we did not consider these further (Violle et al, 2007). Instead, we selected traits based on similar studies investigating succession found using alternate search terms in Google Scholar (Fernández-Martínez et al, 2019;Laine et al, 2018;Monteiro et al, 2020). The selected traits, length, perennation, life form, sporophyte frequency and maximum spore diameter, were extracted from BRYOATT (Hill et al, 2007).…”
Section: Species Traitsmentioning
confidence: 99%
“…An innovative technique that has been proposed consists of vertical greening systems, or Green Walls (Medl et al ). Monteiro et al () studied the effectiveness of green walls in steep slopes under different conditions, by assessing vegetation establishment and spontaneous colonization. Their results validate the use of geotextiles to retain the substrate.…”
Section: The Challenges Of Restoring Quarriesmentioning
confidence: 99%
“…Even under different environmental constraints, the vegetation evolved similarly, benefiting spontaneous colonization by native species, more adapted to local conditions. Monteiro et al () further explored the compositional and functional diversity of vegetation community and found that alleviating limiting conditions (e.g. using irrigation) would only increase functional redundancy.…”
Section: The Challenges Of Restoring Quarriesmentioning
confidence: 99%
“…Sin embargo, hay poca información sobre la contribución de las especies introducidas y las reclutadas de forma natural en la recuperación de canteras, probablemente porque la sucesión espontánea se produce con mayor frecuencia y facilidad en sitios cuyas condiciones ambientales no son muy extremas (Prach y Hobbs, 2008). A pesar de ello, se ha reportado el éxito de la revegetación natural en canteras de caliza (Tropek et al, 2010), minas de arena y de grava (Šebelíková et al, 2020), y muros verdes colocados en paredes verticales de canteras (Monteiro et al, 2020). En otros casos, sin embargo, los parches en regeneración pueden resultar en "desiertos de pioneras", en los que están ausentes las especies características del bosque maduro (De la Peña-Domene et al, 2013), por lo que si estas no se reclutan de manera natural es necesario introducirlas mediante plantaciones que no solo permiten recuperar especies, sino también funciones ecológicas.…”
Section: Introductionunclassified